Architecture and Urban Planning in Spanish - Cazar Almache, Fabián Eduardo; Crespo Fajardo, José Luis (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
Editorial para la revista Estoa 13 (Julio - Diciembre 2018)